Interaction of BTB-TAZ protein MdBT2 and DELLA protein MdRGL3a regulates nitrate-mediated plant growth. Issue 1 (9th February 2021) - Ren, Yi-Ran; Zhao, Qiang; Yang, Yu-Ying; Zhang, Rui; Wang, Xiao-Fei; Zhang, Tian-En; You, Chun-Xiang; Huo, He-Qiang; Hao, Yu-Jin
Abstract: Nitrate acts as a vital signal molecule in the modulation of plant growth and development. The phytohormones gibberellin (GA) is also involved in this process. However, the exact molecular mechanism of how nitrate and GA signaling pathway work together in regulating plant growth remains poorly understood. In this study, we found that a nitrate-responsive BTB/TAZ protein MdBT2 participates in regulating nitrate-induced plant growth in apple ( Malus × domestica ). Yeast two-hybridization, protein pull-down, and bimolecular fluorescence complementation (BiFC) assays showed that MdBT2 interacts with a DELLA protein MdRGL3a, which is required for the ubiquitination and degradation of MdRGL3a proteins via a 26S proteasome-dependent pathway. Furthermore, heterologous expression of MdBT2 partially rescued growth inhibition caused by overexpression of MdRGL3a in Arabidopsis . Taken together, our findings indicate that MdBT2 promotes nitrate-induced plant growth partially through reducing the abundance of the DELLA protein MdRGL3a. Abstract : The BTB-TAZ protein interacts with and promotes ubiquitination and degradation of DELLA protein, thus regulating plant growth in response to nitrate.